Advances in aircraft cabin atmospheric control systems / Ahmad Jais Alias ...[et al.] - Alias, Ahmad Jais; Yatiban, Nasrul Kamil; Salleh, Ramzu; Mohamad, Nor Amidi; Ahmad Shah, Shahrul (2006)
Aircraft technology is one of the most complex technologies and requires detailed and rigorous study. The complexity lies in the numerous systems, equipment and components that are inter-related and cross-functional inside the aircraft. Failure of even a minor system might cause the aircraft not safe to fly or 'grounded '. One of the systems studied in this paper is the Aircraft Cabin Atmospheric Control Systems. The system involves controlling the heating system, cabin cooling or air-conditioning system, pressurization system and oxygen supply system. All the subsystems need to be monitored, controlled and maintained through-out the aircraft life to avoid any inconvenience, harm or even disaster. The paper will discuss the control system in brief, and highlights the current and latest developments in these aircraft systems. Reference to some cases on the effect of the system failure is also included.